Soil-Transmitted Helminth Reinfection and Associated Risk Factors among School-Age Children in Chencha District, Southern Ethiopia: A Cross-Sectional Study - Zerihun Zerdo; Tsegaye Yohanes; Befikadu Tariku (Journal of Parasitology Research)
Mass drug administration (MDA) to the most risky population including school-age children (SAC) is the central strategy to control soil-transmitted helminth (STH) infection. The present study was aimed at estimating the prevalence of STHs reinfection three months posttreatment and associated risk factors among SAC in Chencha district. A cross-sectional study design was employed from April 20 to May 5, 2015, to enroll 408 SAC. Structured questionnaire and Kato-Katz thick smear technique were used to interview parents or guardians and quantify the number of eggs per gram of stool. Pearson chi-square and logistic regression were used to assess the association between predictor variable and STH reinfection. The prevalence of STHs within three months of mass chemotherapy among SAC was 36.8% which is 93.4% of the prevalence (39.4%) before treatment. The estimated prevalence of reinfection (95%CI) for Ascaris lumbricoides, Trichuris trichiura, and hookworms was 23.8% (21.1–28.2), 16.2% (12.7–20.1), and 1.0% (0.3–2.5), respectively. Children of merchant fathers were more likely to be reinfected by STHs in Chencha district. In conclusion, there is rapid reinfection after mass chemotherapy among SAC in Chencha district. Further studies should be carried out to generate cost efficient methods that can supplement mass drug administration to accelerate the control of STHs.